Axiological Aspects of Legal Science from the Muhammadiyah Perspective - Wardiono, Kelik; Junaidi, M; Yuspin, Wardah; Isman, Isman; Rahardjo, Trisno; Hidayat, Syamsul (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study aims to determine the purpose of legal science for Muhammadiyah, specifically the Majelis Tarjih (Islamic Council of Muhammadiyah). This is highly urgent, because the Majelis Tarjih is an entity within Muhammadiyah that is responsible for providing solutions to the problems of the people's lives, especially Muhammadiyah members and Muslims in general. In general, the purpose of legal science is to ensure justice, legal certainty, and benefit. Legal scholars have provided an overview of justice, legal certainty, and benefit. Some argue that law is just if it has legal certainty. Meanwhile, the law is certain if it is written or codified. On the side of benefit, there are also many differences. Is the benefit for the victim only, or for the perpetrator as well? The above matters are constantly experiencing dynamics. Therefore, Muhammadiyah, in this case the Majelis Tarjih, wants to provide an alternative purpose of legal science. Based on this, this research has a fairly high urgency, considering that the Majelis Tarjih in its legal istbath should not deviate from the purpose of the law itself. This research method is normative research with a library approach. The research begins by analyzing Islamic sharia by classifying what is fixed (muthasibat) and what is changeable (muthaghoiroh). These two aspects are then discussed in dialogue with the objectives of sharia (maqasidu shari'ah). In the next stage, the author will study the istinbat method of the tarjih assembly's law to synchronize the objectives of law with the istinbath method of the Muhammadiyah tarjih assembly. The findings of this study are that the objectives of law from the Muhammadiyah perspective are flexible. This flexibility lies in achieving benefits and avoiding harm.